2006
DOI: 10.1158/1535-7163.mct-06-0167
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-dependent and caspase-independent apoptosis induced by evodiamine in human leukemic U937 cells

Abstract: Evodiamine is one of the major bioactive compounds that have been isolated and purified from the fruit of Evodiae fructus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 49 publications
4
69
0
Order By: Relevance
“…Numerous experiments have demonstrated that EVO activated initiator caspases (caspase-8 and 9) and/or effector caspases (caspase-3) to induce the apoptosis in a variety of tumor cell lines including human colorectal carcinoma COLO205 and HT-29 cells (44) and human thyroid cancer cell line ARO (45). In addition, another study showed that EVO promoted translocation of apoptosis-inducing factor (AIF) into the nucleus of human leukemia u937 cells (46). Collectively, EVO was found to induce the apoptosis of many tumor cell lines via caspase-dependent and caspase-independent signaling pathways (47).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experiments have demonstrated that EVO activated initiator caspases (caspase-8 and 9) and/or effector caspases (caspase-3) to induce the apoptosis in a variety of tumor cell lines including human colorectal carcinoma COLO205 and HT-29 cells (44) and human thyroid cancer cell line ARO (45). In addition, another study showed that EVO promoted translocation of apoptosis-inducing factor (AIF) into the nucleus of human leukemia u937 cells (46). Collectively, EVO was found to induce the apoptosis of many tumor cell lines via caspase-dependent and caspase-independent signaling pathways (47).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the cytotoxicity of evodiamine and rutaecarpine on various human cancer cell lines has been extensively studied (Ogasawara at al., 2001;Fei et al, 2003;Liao et al, 2005;Xu et al, 2006;Adams et al, 2007). It has been reported that evodiamine inhibited the proliferation of a wide variety of tumor cells by inducing apoptosis via different mechanisms, including caspase-dependent and -independent pathways, the sphingomyelin pathway, and PI3K/Akt/caspase and Fas-L/NF-kB signaling pathways (Lee et al, 2006a;Kan et al, 2007;Wang et al, 2010;Huang et al, 2011). More recently, highly potent evodiamine derivatives were discovered as novel antitumor agents by systemic structure-activity relationship analysis and biologic evaluations (Dong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been being used for the treatment of gastrointestinal disorders, headache and postpartum hemorrhage (5)(6)(7). Evodiamine is a naturally occurring quinolone alkaloid found in the fruit of Evodia rutaecarpa.…”
Section: Introductionmentioning
confidence: 99%
“…Evodiamine is a naturally occurring quinolone alkaloid found in the fruit of Evodia rutaecarpa. The data of several studies concerning its cytotoxic activity in cancer cells demonstrated that evodiamine inhibited the growth of a wide variety of tumor cells, including breast (8), thyroid (9), liver (10), prostate (11)(12)(13)(14), leukemic T-lymphocyte (5,15), melanoma (6,(16)(17)(18) cervical (19,20), colon (21)(22)(23)(24), colorectal (25) and lung cells (26) through induction of apoptosis, regulation of cell cycle and reduction of invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%